The art of Danish living : how the world's happiest people find joy at work - Wiking, Meik (Abrams Image, an imprint of ABRAMS, 2024)
"A beautiful, research-backed guide on how to work like the happiest people in the world, the Danes. From the author of the million-copy bestseller The Little Book of Hygge. Based on a new study from the Happiness Research Institute, Meik Wiking reveals the main factors that build happiness at work--purpose, trust, relationships, balance, and more--to show how we can reduce stress, increase productivity, and find fulfillment, both in and out of work. It is well known that the Danes have a fantastic work-life balance, that working late is discouraged, parental leave is split equally, and long summer holidays are the norm. They even have a word meaning 'happiness at work'--arbejdsglæde. Meanwhile, the rest of the western world is struggling with a burn-out epidemic--but where are we going wrong? There is an alternative, and The Art of Danish Living will provoke and inspire. "--